On the Unfinished and Uncertain Paths of Logic: The Case of Non-Monotonic Logics - Morales Delgado, Jorge (2025)
In the prologue of the second edition of the Critique of Pure Reason, Immanuel Kant offers a vision of logic as a science completely finished. Nevertheless, further advances have proven this Kantian idea wrong. The current work offers a discussion of non-monotonic logics and some of the philosophical presuppositions as an example of a formal system of very recent development with an interdisciplinary background that allows us to understand a particular class of inferences of human reasoning. In this sense, non-monotonic logics are a paradigmatic case which shows how distant is logic from being a perfect and finished science.